Relationship between Utilization of the MCH Handbook and Mother's Knowledge and Attitudes in Early Detection of Stunting - Dewi Nirmala Sari (GoAcademica Research & Publishing, 2023)
It is important to pay attention to the prevalence of under-five nutritional problems in Indonesia in 2022 which will still reach 21.6%, especially related to stunting and underweight. This disorder has far-reaching consequences, including increased morbidity and mortality. As a result, it is critical to recognize stunting early, and one way that can be done is to employ Maternal and Child Health (MCH) books as a source of information for moms of toddlers. Through this MCH guide, mothers can independently monitor their toddlers' growth and development, as well as expand their understanding and attitudes about toddler nutrition. The purpose of this study is to examine the association between the use of the MCH handbook and the mother's knowledge and attitudes about early stunting identification. The study was a quantitative study that was done out utilizing cross-sectional research methodologies on 88 moms who had toddlers and MCH books. The results showed that the use of the MCH handbook as a communication tool was the factor that had the most influence on mother's knowledge (OR=12,007) and one of the factors that had a significant impact on mother's attitude in early detection of stunting.